Meningkatkan Kinerja Pegawai melalui Disiplin, Komunikasi, Beban kerja dan Kearifan Lokal - Saripuddin Saripuddin; Maryadi Maryadi; Nurhaedah Z Nurhaedah Z (UNIVED Press, 2023)
The design of this research is quantitative research and aims to determine the effect of work discipline, communication, workload and local wisdom on employee performance. The variables used in this study are four independent variables, namely work discipline, communication, workload and local wisdom and one dependent variable, namely employee performance. The types and sources of data used are primary data through questionnaires and secondary data obtained from various sources of information, namely the web, magazines, books, and previous research journals. The population in this study were all Civil Servants of the Makassar City Transportation Service as many as 95 people, with the saturated sample technique, the total sample was 95 respondents. Furthermore, the answers from each instrument were collected through a tabulation process using a Likert scale. This analysis is used to answer the problem by simultaneously testing the hypothesis in this study using multiple linear regression statistical tools. The results of the study found that work discipline, communication and local wisdom had a positive and significant effect on employee performance. While the workload has a negative and significant effect on employee performance.